Cushing's syndrome: an update on current pharmacotherapy and future directions. (August 2015) - Creemers, Sara G; Hofland, Leo J; Lamberts, Steven WJ; Feelders, Richard A
<x xml:space="preserve">Abstract</x> Introduction: Endogenous Cushing's syndrome (CS) is characterized by chronic overproduction of cortisol and is associated with increased mortality and morbidity. It can be caused by a pituitary adenoma, ectopic adrenocorticotropic hormone (ACTH) production or primary adrenal disease. Successful tumor-directed surgery is the keystone treatment. When surgery is unsuccessful, contraindicated or in case of acute disease, pharmacotherapy is indicated to treat hypercortisolism. Areas covered: In this review, pharmacotherapeutic options for CS will be covered discussing the different possible targets, that is: i) inhibition of ACTH secretion; ii) suppression of steroidogenesis; and iii) blockade of cortisol effects at tissue level. Preclinical and clinical studies will be discussed considering mono- and combination therapy, taking into account efficacy, toxicity and mechanism of action. Per CS entity, future directions of pharmacotherapies will be addressed. Expert opinion: The number of medical treatment options for CS has increased in the past years. In contrast to decades ago, prospective trials are now being performed focusing on pituitary-directed drugs like pasireotide, the glucocorticoid receptor blocker mifepristone and 'new generation' steroid synthesis inhibitors. Future studies will focus on tumor-shrinking effects of neuromodulatory drugs, the optimal order and combination of pharmacotherapy, long-term efficacy and safety and new targets for medical treatment of CS.